Precise Examination of Peripheral Vascular Disease for Diabetics with a Novel Multiplexed NIR-II Fluorescence Imaging Technology. (April 2022) - Huang, Haoying; Sun, Zhuqing; Yang, Hongchao; Yang, Xiaohu; Wu, Feng; Sun, Yao; Li, Chunyan; Tian, Mei; Zhang, Hong; Wang, Qiangbin
Highlights: The novel multiplexed NIR-II fluorescence imaging technology is an effective imaging diagnostic method for peripheral vascular disease. The molecular probe V&S@Au:Ag2 Te realizes the specific and sensitive detection of the biomarker ONOO - . The ratiometric fluorescence (FQD /FSY1100 ) presents a quantitative assessment of ONOO - in vivo. The combination of the functional, morphological and multi-parameter molecular analysis prompts the prognosis for diabetic foot ulcers. Graphical Abstract: ga1 Abstract: Patients with chronic diseases, such as diabetes, were suggested to take regular peripheral vascular examination. However, it is still a challenge to provide a cost-effective and community-friendly imaging diagnostic technology for precise multi-parameter detection in all stages of peripheral vascular disease (PVD). Here, we present a study to demonstrate the precise detection for all-phases PVD with a novel multiplexed NIR-II fluorescence imaging technology, which includes a vascular cell adhesive molecule (VCAM-1) targeted and peroxynitrite (ONOO - ) responsive dual-emission nanoprobe V&S@Au:Ag2 Te (VCAM-1 binding peptide & SY1100 @ Au:Ag2 Te quantum dot), a ratiometric correction algorithm, and a systemic examination protocol. The NIR-II fluorescence angiography provided high resolution functional and morphological analysis, and precisely graded the PVD with multi-parameter molecular detection, which could be used to call for reasonable precautions against progress of diabetic foot ulcer. We believe that the novel multiplexed NIR-II fluorescence imaging technology would perform as an important cost-effective and community-friendly imaging diagnostic method for regular peripheral vascular examination for diabetics in the near future.